Dietary formaldehyde: a silent aggravator of diabetes and cognitive impairments - Hanyuan Xu; Haishu Chen; Yihao Li; Tiancheng Luo; Danrui Zhao; Xiaoxiao Chen; Haozhan Zhang; Xinyun Hu; Hui Xu; Yiquan Wang; Yangping Shentu; Zhiqian Tong (Nutrition & Diabetes)
Abstract Diabetes mellitus (DM) is a chronic metabolic disorder associated with a range of serious complications, including insulin resistance (IR) and cognitive impairments. IR is recognized as a high-risk factor for the development of cognitive decline. However, it remains unclear which endogenous or exogenous factors induce these two pathological features. Recent studies indicate that certain diets, environmental pollutants, and genetic deficiencies or polymorphisms influence the metabolism of endogenous formaldehyde. Formaldehyde has been implicated in the onset of DM. Notably, elevated levels of formaldehyde have been detected in the blood, peripheral organs (such as the spleen and liver), and brains of both DM patients and animal models of diabetes. Formaldehyde-induced hyperglycemia and high glucose levels generate formaldehyde, creating a vicious cycle that speeds up diabetic complications. Further, excessive formaldehyde induces IR through three distinct mechanisms: alteration of the biologically active conformation of insulin, reduction in insulin receptor expression, and modification of insulin receptor structure. In addition, excessive formaldehyde can impair cognitive functions by inhibiting N-methyl-D-aspartate (NMDA) receptors and exacerbating brain IR. In this review, we discuss the pivotal role of diet-derived formaldehyde in diabetes and propose that reduction of formaldehyde by the formaldehyde scavengers may be a new strategy for treating DM patients.